Self-Reinforcing Mechanisms and Market Information - Elettra Agliardi; Mark S. Bebbington (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
We consider the possibility of switching between two technological standards when there are network externalities and imprecise market information. Multiple equilibria in terms of market shares can arise. The main result is that lock-in to one of multiple equilibria is not a permanent out- come when the source of lock-in is network externalities. The market lingers at prevalence of one standard with intermittent transitions to prevalence of the other. In other words, lock-in is a temporary occurrence.
Keywords: 330